2016
DOI: 10.5152/tud.2016.18784
|View full text |Cite
|
Sign up to set email alerts
|

2% Lidocaine gel or plain lubricating gel: Which one should be used in male flexible cystoscopy?

Abstract: Objective: To investigate and compare the effects on pain of intraurethral 2% lidocaine gel and plain lubricating gel in male patients underwent flexible cystoscopy. Material and methods:The data of 220 male patients who underwent flexible cystoscopy between March 2012 and August 2014 were retrospectively analized. The patients were divided into 2 groups according to using intraurethral gel types. Group I included 120 patients who were underwent flexible cystoscopy with 2% lidocaine gel and Group II was consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Although it remains to still be a controversial issue, the claim that there is no difference between anesthetic gel and plain one seems more prevalent [11][12][13][14]. Flexible cystoscopy's softness and pliability results in less pain than the rigid one; however, due to technical limitations, such as visual acuity, image quality, or difficulty, it still cannot completely replace the rigid cystoscopy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains to still be a controversial issue, the claim that there is no difference between anesthetic gel and plain one seems more prevalent [11][12][13][14]. Flexible cystoscopy's softness and pliability results in less pain than the rigid one; however, due to technical limitations, such as visual acuity, image quality, or difficulty, it still cannot completely replace the rigid cystoscopy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is currently the most widely used local anesthetic. However, recent studies have shown that lidocaine gel has no obvious advantage over urethra pain control compared with ordinary gel, and may cause additional pain and discomfort [3][4][5]. In addition to the use of anesthetics to relieve pain, more and more attention has been paid to the study of nondrug analgesic methods in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine is currently the most widely used local anesthetic. However, recent studies have shown that lidocaine gel has no obvious advantage over urethra pain control compared with ordinary gel, and may cause additional pain and discomfort [3][4][5]. In addition to the use of anesthetics to relieve pain, more and more attention has been paid to the study of non-drug analgesic methods in recent years.…”
Section: Introductionmentioning
confidence: 99%